The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2147/dddt.s218371
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ubenimex induces apoptotic and autophagic cell death in rat GH3 and MMQ cells through the ROS/ERK pathway</p>

Abstract: PurposeUbenimex, an aminopeptidase N (APN) inhibitor, is widely known for its use as an adjunct therapy for cancer therapy. However, in recent studies, it has also conferred antitumour effects in many cancers, but its anticancer mechanism is largely unknown. This study aims to investigate the specific anticancer activities and mechanisms of ubenimex in GH3 and MMQ cells.Materials and methodsIn this study, we investigated the anticancer effects of ubenimex in GH3 and MMQ cells. Cell viability and cell death wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Indeed, sensitization of cancer cells to chemo-or radiotherapy is largely attributed to enhanced apoptosis of cancerous cells. 44 However, ROS generation can also contribute to tissue damage. This was most recently described in the case of COVID-19, where overabundant ROS promoted sudden patient decline.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sensitization of cancer cells to chemo-or radiotherapy is largely attributed to enhanced apoptosis of cancerous cells. 44 However, ROS generation can also contribute to tissue damage. This was most recently described in the case of COVID-19, where overabundant ROS promoted sudden patient decline.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ubenimex can also induce the death and apoptosis of autophagocytes, which indicates that a mixed type of programmed cell death occurs in bladder tumor cells after ubenimex application. 26 Toshiyama et al 27 Found that ubenimex and fluorouracil, cisplatin or adriamycin had a synergistic effect and played an effective anti-tumor role, without increase in adverse drug reactions. Moreover, ubenimex is also an inhibitor of CD13, which can be used as an immune adjuvant to improve the immune status of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an inhibitor of APN, ubenimex, was reported to induce apoptotic cell death in rat pituitary tumour cells by promoting ROS generation. 52 Therefore, several uorescent probes for imaging of tumour tissues and drug screening through the targeting of APN have been created. 53,54 Li et al 55 reported three ratiometric uorescent probes 9-11 for detecting the activities of APN (Fig.…”
Section: Cancermentioning
confidence: 99%